Is acupuncture "stimulation" a misnomer? A case for using the term " blockade" - Silberstein, Morry (BioMed Central Ltd., 2013)
Background: The term used most frequently in the literature to describe acupuncture's effects is " stimulation" which may be used to describe either (or both) the direct stimulus applied to a needle as well as putative stimulation of the nervous system, despite little published evidence describing what is actually being stimulated. In contrast, recent published work has suggested that acupuncture may, in fact be inhibitory at a peripheral level, acting by blocking neural transmission.Discussion: The suggestion that acupuncture exerts its effects through peripheral neural blockade is supported by recent evidence explaining related techniques including low level laser and capsaicin at acupoints. It also explains acupuncture's effect on painful and non-painful conditions and both Eastern and Western concepts of acupuncture. There is a need for additional work to elucidate acupuncture's mechanism of action, and the suggestion that it acts through neural blockade should prompt further research in this direction.Summary: If the term " blockade" were applied to acupuncture, this would, likely, be expected to promote this minimally invasive technique, and, potentially, bring it into mainstream clinical practice for pain management as well as other therapeutic applications. © 2013 Silberstein; licensee BioMed Central Ltd.